PENERAPAN GCG DALAM IMPLEMENTASI AL-FATIHA PADA PERILAKU ETIS PELAKU USAHA: PENERAPAN GCG DALAM IMPLEMENTASI AL-FATIHA PADA PERILAKU ETIS PELAKU USAHA - Lely Kodarsih; Mohammad Djasuli (CV ODIS, 2022)
The problem studied is that many companies do not understand the implementation of GCG in the implementation of al-Fatiha for business actors to improve the quality of human resources in the future and its impact on company performance. Researchers want to know how the implementation of GCG in a company and how to implement al-Fatiha on the ethical behavior of business actors. This makes the researcher raise the title of GCG Implementation in the implementation of Al-Fatiha on the ethical behavior of business actors. In answering these problems, the researcher used purposive sampling and interview methods. The researcher concludes that the implementation of GCG in the implementation of al-Fatiha on the ethical behavior of business actors affects the company's performance in the future to improve the quality of better human resources.